The effect of ratio of Soursop Juice with Passion Fruit Juice and Concentration of Arabic Gum on The Quality of Coconut Water Sorbet - Ririn Carolina Silalahi; Ismed Suhaidi; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Coconut water from ripe coconut are side product and rarely used in small amount. The aim of this research was to find the effect of ratio of Soursop Juice with Passion Fruit Juice and Concentration of Arabic Gum on The Quality of Coconut Water Sorbet. This research had been conducted using factorial completely randomized design with two factors, i.e ratio of soursop juice with passion fruit juice (B): (80%:20%, 60%:40%, 40%:60%, 20%:80%) and concentration of arabic gum (G): (0%,0,1%, 0,2%, 0,3%). Parameters analized were vitamin C content, total acid, total soluble solid, fiber content, melting speed, organoleptic of color, flavor, taste and texture. The results shows that the the effect of ratio of soursop juice with passion fruit juice had highly significant effect on vitamin C content, total acid, total soluble solid, fiber content, melting speed, organoleptic of color, flavor, taste and texture. Ratio of soursop juice with passion fruit juice of (20%:80%) produced the best coconut water sorbet and more acceptable. Arabic gum of 0,3% produced the best coconut water sorbet. Keywords : Arabic gum, Coconut water sorbet, passion fruit, soursop.